INTEGRATION OF CHARACTER VALUES IN LEARNING PANCASILA AND CITIZENSHIP EDUCATION (PPKn) IN STRENGTHENING THE MORAL OF THE NATION - Yeyeng, Andi Tenri; Lutfi, Muchtar; Yaumi, Muhammad; Tajuddin, Muhammad Saleh (Jurnal Diskursus Islam, 2021)
This paper discusses the integration of character values in Pancasila and Citizenship Education (PPKn) subject. This integration needs to be done considering the increasing number of national problems, such as brawls, drug abuse, corruption, money politics, abuse of authority, and so on. Several character values such as religious values, love for the country, democracy, honesty, hard work and others need to be integrated into PPKn learning. So far, PPKn studies have only been studied with regard to cognitive aspects, while affective and psychomotor aspects have not been given sufficient space to improve student character scores. Strategic and methodological rarities are needed such as planning, implementing and evaluating PPKn learning. As a recommendation to every educator to improve their knowledge, skills, and methodological abilities such as workshops and further study.